Breastfeeding experiences of female physicians and the impact of the law change on breastfeeding - (:unkn) unknown (TURKISH PEDIATRICS ASSOC, 2019)
Aim: A recent improvement was made on the law regulating maternity leave in 2011 in Turkey. The leave without pay period was increased, the right to stop working on night shifts was granted, and work hours were improved. It is a known fact that returning to work is a barrier against exclusive and total breastfeeding duration. Legal regulations have crucial importance on the ability of working mothers to breastfeed their infants. The aim of this study was to calculate the effect of the improved law on breastfeeding rates among female physicians. Moreover, the difference in the duration of exclusive breastfeeding and total breastfeeding were evaluated in relation to the new law. Material and Methods: Three of the major hospitals in Istanbul were included in the study. A pilot study was planned and our questionnaire was tried. The actual study included 40 female physicians from each hospital. Mothers who went through antenatal or postnatal complications were excluded from the study. Infants who required intensive care after birth or were never breastfed were similarly excluded. A total of 109 female physician resident mothers' questionnaires were included in the study. Results: The effects of the improvement in the law were statistically significant on the duration of maternity leave and improved working hours after returning to work (OR: 2.74 and OR: 2.52). Exclusive breastfeeding rates and total breastfeeding for more than 12 months significantly increased after the new law (OR: 4.47 and OR: 256). Conclusions: This study showed that legal improvements did reflect on positive outcomes. There is more to be done, especially with condition of the work places and distributing rights equally to women practicing in surgical disciplines as well. If the physicians can breastfeed after they become mothers, their experience may affect their breastfeeding advocacy and the guidance they will provide for their patients.
Keywords: Breastfeeding; physicians; law; MOTHERS; WORK; BEHAVIOR